Tackling Virus Resistance - International Potato Center (2014)
Sweet potato virus disease (SPVD) resistant parents have been included in two crossing blocks, one with 80 parents and a smaller one with 50 parents at Namulonge in Uganda. The two populations (in physically separated crossing blocks) were previously differentiated on the basis of simple sequence repeat (SSR) markers. The crossing blocks have been used to generate populations for SPVD resistance and molecular marker development. The procedure to discriminate SPVD susceptible, tolerant and resistant varieties has been optimized.